Dizzy - Winter, Jonah; Qualls, Sean (New York : A.A. Levine, 2006)
Simple text and illustrations introduce the life of jazz musician Dizzy Gillespie.
Notable/Best Books (A.L.A.)
School Library Journal starred
Wilson's Children
4.6
K-3
K-3
Keywords: Gillespie, Dizzy, -- 1917-1993 -- Juvenile literature; Gillespie, Dizzy, -- 1917-1993.; Gillespie, Dizzy, -- 1917-1993.; Jazz musicians -- United States -- Biography -- Juvenile literature; African Americans -- Biography; Jazz musicians; African Americans -- Biography; Jazz musicians -- Biography